Epstein-Barr Virus (EBV) DNA in Sera of Patients with Primary EBV Infection - Chan, K. H. (American Society for Microbiology, 2001)
Detection of Epstein-Barr Virus (EBV) DNA by PCR in serum had a sensitivity of 80%, a specificity of 94%, and positive and negative predictive values of 95 and 79%, respectively, for the diagnosis of primary EBV infection. We suggest that this is a useful addition to the panel of tests used for this purpose.